Investigating EFL Teacher's Strategies Ini Teaching Reading Comprehension - Fazriah, Lusiana; Al-Baekani, Abdul Kodir; Nugraha, Sidik Indra (Pascasarjana Universitas Negeri Makassar, 2025)
This qualitative case study investigates how an Indonesian junior-secondary EFL teacher coordinated three complementary practices brief fluency work (listen-and-repeat/echo reading), explicit Question–Answer Relationships (QAR), and responsive scaffolding to improve students’ reading comprehension during routine lessons. Motivated by persistent national concerns about low reading performance and classroom reports of word-by-word translation, limited vocabulary, and uneven decoding, the study documents how supports were sequenced across pre-, during-, and post-reading phases and adapted in real time. Data comprised classroom observations, teacher interview, and instructional artifacts, analyzed using Miles and Huberman’s interactive model (data condensation, display, and conclusion drawing/verification). Findings indicate that short, well-modeled echo-reading segments functioned as fluency “bridges,” freeing working-memory resources for meaning-focused tasks; QAR provided a simple classroom metalanguage that redirected attention from keyword matching toward evidence-based inference (Right There, Think and Search, Author and Me); and contingent scaffolds (sentence frames, think-alouds, prompts to cite lines) were introduced “just in time” and deliberately faded as control emerged. Students increasingly justified answers with textual citations and combined ideas across sentences, signaling movement from literal retrieval to local integration. Practical design principles include planning for dual bottlenecks (lexis and processing) via paired fluency-plus-vocabulary warm-ups, making QAR the spine of during-reading talk, using micro-diagnostics to localize breakdowns, and aligning assessment with literal, integrative, and inferential demands. Limitations relate to the single-case context and absence of standardized pre–post measures; future work should test the approach across genres and cohorts with validated outcomes. Overall, the study offers a feasible, theory-aligned orchestration of strategies for strengthening EFL reading comprehension in resource-constrained secondary classrooms.